(untitled) (Revista Científica Integrada, 2025)
Objective: To analyze the patterns and contextual determinants of maternal mortality among indigenous women in Brazil from 2020 to 2024. Method: This is an ecological study using data from the Brazilian Obstetric Observatory. The analysis was conducted in a descriptive manner where measures of central tendency were calculated, carried out in the R software. Results: It was observed that brown and black women represent the highest proportions, corresponding to 53% and 12%, respectively. The proportion of indigenous women is significant in the North (58%). Direct deaths predominated, accounting for 52% of cases, while indirect deaths accounted for 45%. The immediate puerperium was the period with the highest concentration of deaths (61%), although 84% of women received care, there were few autopsies (9.7%) and death investigations (22%). Conclusion: The study highlights the urgency of interventions to reduce racial inequalities. By prioritizing cultural and social specificities, public policies can guarantee equitable access to health and prevent avoidable deaths. Keywords: Intersectionality; Women’s Health; Indigenous Population Health; Maternal Mortality; Health Information Systems